Malacología Latinoamericana: Moluscos de agua dulce de Argentina - Alejandra Rumi; Diego E Gutiérrez Gregoric; Verónica Núñez; Gustavo A Darrigran (Revista de Biología Tropical, 2008)
Se presenta un estado de situación y una lista actualizada y comentada sobre las especies de moluscos de agua dulce de la República Argentina. Se aborda en Gastropoda y Bivalvia la distribución a nivel de familias; las entidades endémicas, exóticas, invasoras y de importancia sanitaria. Los moluscos relacionados a la cuenca del Plata presentan la mayor riqueza específica. Base de datos: 4 500 registros relevados de las tres colecciones más importantes de la Argentina: MLP, MACN y FML. Además, se incluye información de recolecciones actuales y localidades citadas por otros autores. Hasta el presente han sido descritas 166 especies. De ellas 101 pertenecen a 10 familias de Gastropoda y 65 a 7 de Bivalvia. Las familias que presentan mayor riqueza específica son Lithoglyphidae (22) y Sphaeriidae (25), respectivamente. Sphaeriidae, Cochliopidae, Chilinidae y Lymnaeidae se distribuyen prácticamente en todo el país. Erodonidae y Solecurtidae se registran en ambientes mixohalinos de la provincia de Buenos Aires. Thiaridae y Glacidorbiidae presentan una distribución muy restringida. Especies endémicas de la Argentina: Gastropoda: Ampullariidae (1), Cochliopidae (10), Lithoglyphidae (11), Thiariidae (3), Chilinidae (11), Lymnaeidae (2) y Physidae (2?); Bivalvia: Hyriidae (1?); Etheriidae (1?) y Sphaeriidae (10). Especies de interés sanitario: propagadoras de: Esquistosomiasis, Biomphalaria peregrina, B. straminea y B. tenagophila (Planorbidae); Fasciolasis, Lymnaea viatrix y L. columnella (Lymnaeidae); y dermatitis esquistosómicas, Chilina gibbosa y C. fluminea (Chilinidae). Especies de origen asiático: Corbicula fluminea (Corbiculidae) y Limnoperna fortunei (Mytilidae). Es prioritaria la formación de áreas protegidas para la conservación de especies endémicas, especialmente de la Mesopotamia Argentina. Latin American Malacology. Freshwater Mollusks from Argentina. A report and an updated list with comments on the species of freshwater molluscs of Argentina which covers an area of 2 777 815 km² is presented. Distributions of Gastropoda and Bivalvia families, endemic, exotic, invasive as well as entities of sanitary importance are also studied and recommendations on their conservation are provided. Molluscs related to the Del Plata Basin have been thoroughly studied in comparison to others areas of the country. This fauna exhibits relatively the biggest specific richness and keeps its affinity with the fauna of other regions of the basin in areas of Paraguay and Brasil. The 4 500 records of molluscs considered in this paper arise from the study of the collections of Museo Argentino de Ciencias Naturales "Bernardino Rivadavia", Buenos Aires; Museo de La Plata, La Plata and Fundación "Miguel Lillo", Tucumán. These institutions keep very important collections of molluscs in southern South America. Field information has recently been obtained and localities cited by other authors are also included in the data base. Until today, 166 species have been described, 101 belonging to 10 families of Gastropoda and 65 to 7 of Bivalvia. Families with highest specific richness are Lithoglyphidae (22) and Sphaeriidae (25), respectively. The number of endemic species (those present only in Argentina) by family is: Gastropoda: Ampullariidae (1), Cochliopidae (10), Lithoglyphidae (11), Thiariidae (3), Chilinidae (11), Lymnaeidae (2) and Physidae (2?); Bivalvia: Hyriidae (1?); Etheriidae (1?) and Sphaeriidae (10). Families with a distribution that comprise almost the whole country are: the Sphaeriidae and the gastropods Cochliopidae, Chilinidae and Lymnaeidae. Families Erodonidae and Solecurtidae (Bivalvia) were registered in mixohaline environments from Buenos Aires province. Gastropod families Thiaridae and Glacidorbiidae show a very restricted distribution. The rest of the families are present mainly in the center and north of the country. Species of sanitary interest are the propagators of: schistosomiasis -Biomphalaria peregrina, B. straminea y B. tenagophila, Planorbidae-, fasciolasis -Lymnaea viatrix and L. columnella, Lymnaeidae- and dermatitis -Chilina gibbosa and C. fluminea, Chilinidae. Invasive species are: Corbicula fluminea (Corbiculidae) and Limnoperna fortunei (Mytilidae). The construction of new areas for the protection and conservation of the high risk endemic species of freshwater molluscs is a priority. It is necessary to give special attention to the species of the patagonic mountain range and of the mesopotamic area of the Del Plata Basin. Rev. Biol. Trop. 56 (1): 77-111. Epub 2008 March 31.